Disability alliances and allies : opportunities and challenges - Carey, Allison C.; Ostrove, Joan M.; Fannon, Tara (Research in social science and disability, 2020)
In Disability Alliances and Allies: Opportunities and Challenges, Allison Carey, Joan Ostrove and Tara Fannon have gathered an interdisciplinary team of leading experts, to offer nuanced analyses of the meaning and practice of being an ally and of building effective alliances that account for the structural, individual, and interpersonal challenges involved in amplifying disabled voices and centering the disability lived experience. The first section of this volume addresses cooperation and conflict in advocacy and activism across social movements, organizations, and institutions. It examines the formation of new alliances, what happens when interests collide, and the social and economic challenges of forming coherent unions. The second section engages issues of agency, autonomy, and identity in interpersonal relationships, highlighting the role of power and status, focusing on alliance dynamics between disabled and non-disabled people. For its breadth and depth of research, this volume of Research in Social Science and Disability is essential reading for researchers and students across the social sciences interested in disability, social movements, activism, and identity.